2006
DOI: 10.1128/ec.5.3.457-468.2006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Phosphoproteome of Chlamydomonas reinhardtii Provides New Insights into Various Cellular Pathways

Abstract: The unicellular flagellated green alga Chlamydomonas reinhardtii has emerged as a model organism for the study of a variety of cellular processes. Posttranslational control via protein phosphorylation plays a key role in signal transduction, regulation of gene expression, and control of metabolism. Thus, analysis of the phosphoproteome of C. reinhardtii can significantly enhance our understanding of various regulatory pathways. In this study, we have grown C. reinhardtii cultures in the presence of an inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…Phosphorylation of the C. reinhardtii SOUL/HBP at two sites of its N terminus (Thr-42 and Ser-44) might play a role for its heme-binding capacity, since His and Cys possibly involved in the necessary complexation of Fe 21 in the heme are also situated at the N terminus (T. Schulze and M. Mittag, unpublished data). A second Chlamydomonas SOUL/HBP (ID 154433; Vs2), which is not present in the eyespot proteome, is also phosphorylated at the N terminus (Ser-2 and Ser-3; Wagner et al, 2006). Also a predicted unusual protein kinase (ID 153985) could be involved in signaling events.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Phosphorylation of the C. reinhardtii SOUL/HBP at two sites of its N terminus (Thr-42 and Ser-44) might play a role for its heme-binding capacity, since His and Cys possibly involved in the necessary complexation of Fe 21 in the heme are also situated at the N terminus (T. Schulze and M. Mittag, unpublished data). A second Chlamydomonas SOUL/HBP (ID 154433; Vs2), which is not present in the eyespot proteome, is also phosphorylated at the N terminus (Ser-2 and Ser-3; Wagner et al, 2006). Also a predicted unusual protein kinase (ID 153985) could be involved in signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen of the phosphoproteins were identified by a single phosphopeptide and 16 were covered by more than one, with up to nine phosphopeptides (Table I), where slightly different peptides with overlapping sequences or identical peptides with different phosphorylation sites are also counted. From the identified 33 phosphoproteins in this study, only six were previously described in phosphoproteomic approaches to wholecell extracts and thylakoids of C. reinhardtii (Table II; Turkina et al, 2006b;Wagner et al, 2006) and an additional three were found when comparing the phosphoproteins from Supplemental Table S2. Thus, most phosphorylation sites described here are novel.…”
Section: Identification Of Phosphopeptides From the Eyespot Fraction mentioning
confidence: 99%
See 3 more Smart Citations